Pengaruh Popularitas dan Daya Tarik Influencer terhadap Minat Beli Generasi Z pada Platform Media Sosial - Septi Putri Anggraini; Callista Vania; Mafluhi Ardian Haq Ahlada; M Hasby Azril Firmansyah; Binti Nur Asiyah (MABIS Jurnal Manajemen Bisnis Syariah, 2026)
The rapid growth of social media has transformed digital marketing practices through the use of influencers as promotional media capable of shaping consumer behavior, particularly among Generation Z. As active social media users, Generation Z tends to rely on influencers' recommendations when making purchasing decisions. This study aims to examine the influence of influencer popularity and influencer attractiveness on Generation Z's purchase intention through social media. A quantitative approach with an associative research design was employed. Primary data were collected through an online questionnaire distributed to 56 Generation Z respondents selected using purposive sampling. The data were analyzed using SPSS version 26, including validity and reliability tests, classical assumption tests, multiple linear regression, partial (t-test), and simultaneous (F-test) analyses. The findings indicate that both influencer popularity and influencer attractiveness have a positive and significant effect on Generation Z's purchase intention, both partially and simultaneously. Influencer attractiveness emerged as the most dominant factor, suggesting that authenticity, personality, and communication style play a more important role in fostering consumer trust and purchase intention than popularity alone. These findings imply that businesses should consider both the credibility and attractiveness of influencers when developing effective digital marketing strategies targeting Generation Z..